2019
DOI: 10.1002/jbm.a.36708
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic effect of chemical and topological signals of gingival regeneration scaffold on the behavior of human gingival fibroblasts

Abstract: Achievement of gingiva regeneration poses a substantial challenge for dental aesthetics and periodontal disease repair, but reports of a bioactive and easily available gingival regeneration scaffold are rare. Cell behaviors can be affected by multiple kinds of bioactive signals; thus, it is important to explore the effects of the chemical and topological signals of the scaffold on the behavior of human gingival fibroblasts (HGFs). We hypothesized that the synergetic effect of the chemical and topological scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Yang found that aligned scaffold group showed higher HGF cell proliferation than the random scaffold group. 120 The same results were obtained with dental follicle stem cells (DFSCs) 186 and BMSCs. 187 Besides, the orientation of fibers also affects the arrangement and differentiation of cells.…”
Section: Orientationsupporting
confidence: 57%
See 2 more Smart Citations
“…Yang found that aligned scaffold group showed higher HGF cell proliferation than the random scaffold group. 120 The same results were obtained with dental follicle stem cells (DFSCs) 186 and BMSCs. 187 Besides, the orientation of fibers also affects the arrangement and differentiation of cells.…”
Section: Orientationsupporting
confidence: 57%
“…24,110 In previous study, human gingival fibroblasts (HGF) grew faster on pDA-coated PCL electrospun scaffolds, which means the great potential application of coating in the usage of periodontal tissue regeneration. 120 However, its effect on different cells varies. Lin reported that coating pDA on fibers brought no benefit to the adhesion, proliferation and osteogenic differentiation of TSPCs.…”
Section: Surface Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gingiva recession is one of the common oral diseases, and the decrease of proliferation and function of hGFs are an important reason of gingiva recession 26,27 . The aging of hGFs is an important reason for the decline of cell repair ability and anabolic ability, while phenytoin can stimulate the proliferation and anabolic ability of hGFs 28‐30 . In this study, we found that phenytoin can be used as a potential drug to interfere with hGFs aging in vitro.…”
Section: Discussionmentioning
confidence: 71%
“… 26 Besides, porous scaffolds with desired properties, such as proper mechanical property, good inner pore architecture, and appropriate bioactivity, are highly demanded for tissue regeneration. 27 , 28 Therefore, numerous scaffolds were developed with synthetic or natural polymers using a lot of techniques including phase separation, 29 solvent casting-particulate leaching, 30 fiber meshes, 31 gas foaming, 32 , 33 rapid prototyping, 34 and a series of three-dimensional (3D) or four-dimensional (4D) printing approaches. 35 , 36 Among these technologies, one of the attractive advantages of phase separation is that a highly interconnected porous structure can be controllably and scalably formed by simply regulating the fabrication parameters, such as polymer concentration, temperature, etc, and bioactive compounds can be directly incorporated without affecting intrinsic biological function.…”
Section: Introductionmentioning
confidence: 99%